Lead toxicity on a sentinel species subpopulation inhabiting mangroves with different status conservation - Duarte, Luis Felipe de Almeida; Blasco, Julián; Catharino, Marília Gabriela Miranda; Moreira, Edson Gonçalves; Trombini, Chiara; Nobre, Caio Rodrigues; Moreno, Beatriz Barbosa; Abessa, Denis Moledo de Souza [UNESP]; Pereira, Camilo Dias Seabra (Elsevier, 2020)
Lead is a priority pollutant introduced in the aquatic environment by different sources commonly located in estuarine regions, such as ports, marinas and industries. Environmental agencies around the world set the maximum allowable concentration of lead in effluents, surface water and sediment, but few studies reported its accumulation and chronic toxicity in mangrove benthic invertebrates using concentrations believed to be safe. In the case of Brazilian mangrove environments, Ucides cordatus is a crab species of choice to be used in bioaccumulation studies. We have assessed biomarkers’ responses (DNA strand breaks, micronucleated cells, metallothioneins, enzymatic activity of aminolevulinic acid dehydratase and neutral red retention time) and the total bioaccumulation in six tissues of U. cordatus crabs resident to mangrove areas under different conservation status during a 28-day period bioassay. We also investigated Pb subcellular partition and biomarkers’ responses using a supposedly safe concentration (10 μg L−1). During the Pb exposure, the highest concentration of Pb was observed in crab gills. Crabs also showed a high ability to allocate Pb in detoxified forms. Multivariate analysis pointed out that bioaccumulation (total, active and detoxified) is linked to biomarkers. Even in supposedly safe dosage, U. cordatus triggered its defense mechanisms expressing more metallothioneins and presented relevant cyto-genotoxic damage. Our data suggest the development of biological tolerance to Pb in crabs from polluted areas. Our results provided a new insight about lead toxicity even at concentrations considered environmentally safe, which could support new strategies to manage estuarine areas considering their respective conservation status.
Keywords: Biomarkers; Cytotoxicity; Genotoxicity; Lead; Subcellular metal partitioning; Ucides cordatus